An empirical study on the reading response to picture books of children aged 5–6 - Wang, Defeng; Su, Min; Zheng, Yiyi (Frontiers in Psychology, 2023)
Picture book reading has drawn a great deal of attention, while the reading response to children’s book has barely been noticed. This study therefore used the lag sequence analysis method to conduct an empirical study on the reading reaction of 60 5-6-year old children during collective picture book reading activities. Results indicated that the children had rich and diversified reading responses which mainly consisted of language description and emotional experience rather than careful observation of the picture books and in-depth understanding of the relationship between the pictures and text. In addition, the children’s oral expression and vocabulary are important predictors of differences in the reading responses of children with different reading abilities. "Image observation to personal empirical reaction" is also the key behavioral sequence that distinguishes children with different reading abilities. Teachers should create a supportive, spiral reading and discussion environment, respect young children readers, pay attention to cultivating visual literacy, and effectively analyze children's reading responses, thereby helping children become true readers who can adapt to the social needs in the future.